Robust design of forming processes - Gantar, Gašper (Strojniški vestnik, 2008)
Properties of raw materials (sheet metal, bars, etc.) used in forming processes are not constant. Other input parameters of forming system (friction conditions, machine settings, temperature, etc.) also scatter considerably during production. Improvement of production processes has always been an important goal in metal forming industry. The aim is to develop cost effective and stabile forming processes where the number of non-conforming products (scrap) is reduced to the minimum. In the first part of the paper an approach is described which enables the user to predict how the scatter of input parameters would influence the final properties of the products. In the second part of the paper the developed approach is used for optimization of forming process with respect to uncontrollable scatter of input parameters with the aim of minimizing scrap ratio. Optimization is basedon the use of numerical simulations, response surface methodology and stochastic optimization. It can be performed in the early stage of the production process development cycle. The presented approach was successfully applied in industrial environment during development of technology for forming of various work pieces.
Keywords: preoblikovalni procesi; preoblikovanje; numerične simulacije; optimiranje